Combined First-Trimester Screening in Northern Finland: Experiences of the First Ten Years - Merilainen Anna; Peuhkurinen Sini; Honkasalo Timppa; Laitinen Paivi; Kokkonen Hannaleena; Ryynanen Markku; Marttala Jaana (SAGE Publishing, 2014)
Objective To evaluate the efficacy of first trimester combined screening for Down's syndrome in Northern Finland during the first 10 years of practice. Methods During 1 January 2002 to 31 December 2011, 47,896 women participated voluntarily in combined screening during first trimester. The risk cutoff was 1:250. The study period was divided into two time periods; 2002-2006 and 2007-2011. Results During the first half of the study period, the detection rate (DR) was 77.3% with a 4.9% false-positive rate (FPR). During the latter half, the DR was 77.1% with a 2.8% FPR. Conclusions An important issue is the number of invasive procedures needed to detect one case of Down's syndrome. The screening performance improved markedly in the latter five years period since the FPR lowered from 4.9% to 2.8% and the number of invasive procedures needed to detect one case of Down's syndrome lowered from 15 to 11.